Analisis Keterlambatan dan Efektifitas Kinerja Bongkar Muat Petikemas Terhadap Pendapatan Terminal Mirah - Nur Widyawati; Erlien Hinriyani (Sekolah Tinggi Maritim Yogyakarta, 2020)
This research was carried out with the aim to determine the delay and effectiveness of container loading and unloading performance, to determine the income earned by the Surabaya terminal of the Tanjung Perak branch. The research design used is quantitative. Data analysis technique used in this study is multiple linear regression analysis, with the aim to determine the effect of delays and the effectiveness of container loading and unloading performance on revenue of mirah terminal at PT. Pelabuhan Indonesia III (Persero) Tanjung Perak Branch. Based on the results of the analysis and discussion, that the delay variable (X1) has a significant relationship to income (Y), the effectiveness of loading and unloading performance variables partially has a significant effect on revenue and delay (X1) and effectiveness loading and unloading performance (X2) simultaneously (simultaneous) has a significant relationship to the income variable (Y).